PENGARUH MINAT BELAJAR DAN SEMANGAT BELAJAR SISWA MTS NEGERI TERHADAP HASIL BELAJAR BACA AL-QUR’AN DI KABUPATEN KAMPAR - Mhd. Yuras; Zulbaida Zulbaida (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
This research aims to find out the effect of learning interest and learning spirit on the learning outcomes of Al-Qur’an reading. The type of this research was field research with quantitative approach. The samples of this research were students of State Islamic Junior High School in Kampar Regency in the amount of 93 students. The data collection techniques used were questionnaire, documentation, and interview. Data analysis in this research used Multiple Linear Regression Technique. The results of this research show that: 1) the learning interest has significant effect on Al-Qur’an reading learning outcomes of State Islamic Junior High School students in Kampar Regency. This was proved by the result of t test where tcount is bigger than ttable namely 7,792 > 1,987, with significant value 0,00 < 0,05 and contributes 40%; 2) learning spirit has significant effect on Al-Qur’an reading learning outcomes of State Islamic Junior High School Students in Kampar Regency. This was proven by the result of t test, where tcount is bigger than ttable namely 12,134 > 1,987, with significance value 0,00 < 0,05 and contributes 61.8%; 3) learning interest and learning spirit altogether have significant effect on Al-Qur’an reading learning result of State Islamic Junior High School Students in Kampar Regency. This was proven by the result of Fcount bigger than Ftable namely 75,140 > value of F table 0,310 and contribute 62.50%. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Japanese Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Japanese to EnglishPRO Never translate Japanese Never translate ejournal.uin-suska.ac.id